Coordinated portfolio investment survey guide - International Monetary Fund; international Monetary Fund. Statistics Department (Washington, D.C International Monetary Fund (IMF), 2018)
This third edition of the Coordinated Portfolio Investment Survey Guide has been prepared to assist economies that participate or are preparing to participate in the Coordinated Portfolio Investment Survey (CPIS). It builds on and updates the second edition of the CPIS Guide (2002) to reflect the adoption of the Balance of Payments and International Investment Position Manual, sixth edition (BPM6) as the standard framework for compiling cross-border position statistics. (IMF page)
1 Introduction -- 2 Scope and Modalities -- 3 Concepts and Principles-- 4 Collection Methods -- 5 Undertaking a Portfolio Investment Survey -- 6 Experience in Conducting the CPIS
"Completed by a team from the IMF Statistics Department."--Title page verso.
includes Bibliographical references
Keywords: Investment and investments; INVESTMENTS; SECURITIES; Portfolio management